Isotopic Signature (δ13C, ∆14C) of DIC in Sediment Pore Waters: An Example from the Rhone River Delta. Issue 5 (19th November 2018) - Dumoulin, J-P; Pozzato, L; Rassman, J; Toussaint, F; Fontugne, M; Tisnérat-Laborde, N; Beck, L; Caffy, I; Delqué-Količ, E; Moreau, C; Rabouille, C
ABSTRACT: A better understanding of the dynamics of different particulate organic matter (OM) pools in the coastal carbon budget is a key issue for quantifying the role of the coastal ocean in the global carbon cycle. To elucidate the benthic component of this carbon cycle at the land-sea interface, we investigated the carbon isotope signatures (δ 13 C and ∆ 14 C) in the sediment pore waters dissolved inorganic carbon (DIC) in addition to the sediment OM to constrain the origin of the OM mineralized in sediments. The study site is located at the outlet of the Rhône River (Mediterranean Sea), which was chosen because this river is one of the most nuclearized rivers in Europe and nuclear 14 C can serve as a tracer to follow the fate of the OM discharged by the river to the coastal sea. The ∆ 14 C results found in the pore waters DIC show a general offset between buried and mineralized OM following a preferential mineralization model of young and fresh particles. For example, we found that the sediment OM has values with a mean ∆ 14 C=–33‰ at sampling stations near the river mouth whereas enriched ∆ 14 C values around +523‰ and +667‰ respectively were found for the pore waters DIC. This indicates complete mineralization of a riverine fraction of OM enriched in 14 C in the river conduit during in-stream photosynthesis. In shelf sediments, the ∆ 14 C of pore waters DIC is slightly enriched (+57‰) with sediment OM reaching –570‰. A mixing model shows that particles mineralized near the river mouth are certainly of riverine phytoplanktonic origin whereas OM mineralized on the shelf is of marine origin. This work highlights the fact that pore waters provide additional information compared to sediments alone and it seems essential to work on both pools to study the carbon budget in river prodelta.